(untitled) (Филолошки студии, 2019)
The present paper focuses on the process of verbalization in the contemporary Russian language. Denominal verbs are seen as the most economic way of expressing meaning compared to normal verbs, therefore in our opinion the increase in their quantity in Russian is caused by the effect of the language economy law. The reasons for language economy are both linguistic and extra linguistic, particularly, the appearance of new information technologies, the internet communication, acceleration of life pace. The article presents the classification of Russian denominal verbs and explores the influence of generic and particular knowledge of interlocutors on the right understanding of the verb meaning. It gives some examples of well-established and occasional denominal verbs and shows the peculiarities of their functioning.